Negative active material, preparation thereof, negative pole piece, battery and device
By covering the graphite surface with amorphous carbon and controlling the crystal phase ratio of the graphite, a specific core-shell structure is formed, which solves the capacity attenuation problem caused by the embeddedness of solvated lithium ions between graphite layers in lithium-ion batteries, and significantly improves the cycle life and performance of the battery.
Patent Information
- Application Number
- CN202311100005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
AI Technical Summary
Natural graphite is a negative electrode material for lithium-ion batteries that easily cause solvation of lithium ions in the electrolyte containing propylene carbonate, resulting in capacity attenuation, and reducing the amount of propylene carbonate will affect rate performance and low-temperature discharge performance.
The core-shell structure of graphite and amorphous carbon coating is used as the negative electrode active material, and the ratio of I3R (101) and I2H (101) of graphite is controlled by isostatic pressure and heat treatment technology to form a specific structure to inhibit the co-embedding of solvent molecules.
It significantly reduces the attenuation of the battery's circulation capacity, improves the cycle life of the lithium-ion secondary battery, and maintains excellent rate performance and low-temperature discharge performance.
Smart Images

Figure BDA0004425276040000111 
Figure BDA0004425276040000121
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode active material, in particular to a negative electrode active material, preparation thereof, a negative electrode sheet, a battery and a device, and belongs to the field of batteries. Background Art
[0002] Natural graphite has the advantages of high capacity and low cost as negative electrode material for lithium-ion batteries, but the problem that limits its widespread application is that in electrolytes containing propylene carbonate, solvated lithium ions are easily embedded in the graphite layers, causing the graphite sheets to peel off and thus capacity decay. In order to avoid the co-embedding of solvent molecules, when using natural graphite as the negative electrode, the content of propylene carbonate in the electrolyte is generally reduced, or other solvents are used instead. However, propylene carbonate has the advantages of high dielectric constant and low melting point as an electrolyte solvent. Reducing its dosage will deteriorate the rate performance and low-temperature discharge performance of lithium-ion batteries.
[0003] Patent document CN102224623A discloses a non-aqueous electrolyte secondary battery that inhibits the decomposition of propylene carbonate. The secondary battery has a negative electrode containing graphite particles as a negative electrode active material and a non-aqueous electrolyte containing propylene carbonate as a non-aqueous solvent. The surface layer of the graphite particles contains a plurality of crystalline regions and amorphous regions of a carbon hexagonal network plane stacked along the surface orientation, and the end face of the carbon hexagonal network has a ring exposed on the surface of the graphite particles. At least a portion of the ring forms a stack of multiple rings, and the average stacking number of the ring exceeds 1 but is less than 2. The amorphous carbon content on the surface of the graphite particles in this scheme is low, and some of the end faces of the carbon hexagonal network are still exposed to the electrolyte, resulting in a large BET, a high irreversible capacity of the battery for the first charge and discharge, and some solvents are still co-embedded during the battery cycle, resulting in fast cycle capacity decay. In addition, defects on the basal plane exposed on the surface of the graphite particles will also cause solvent co-embedding, resulting in capacity decay.
[0004] Therefore, there is an urgent need to develop novel anode active materials with excellent cycling performance. Summary of the invention
[0005] In order to overcome the technical defect of fast capacity decay caused by using existing graphite as negative electrode active material of lithium ion battery, the present invention provides a negative electrode active material which can inhibit the co-embedding of solvated lithium ions into graphite layers and a lithium ion secondary battery comprising the negative electrode active material.
[0006] A first aspect of the present invention provides a negative electrode active material, which includes graphite and a coating layer located on the surface of the graphite and including amorphous carbon, wherein the graphite satisfies the following relationship: 0.25≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101))≤0.5, wherein the I 3R(101) is the peak intensity of the X-ray diffraction peak of the rhombohedral phase 101 crystal plane of graphite in the negative electrode active material, wherein I 2H(101) is the peak intensity of the X-ray diffraction peak of the hexagonal phase 101 crystal plane of graphite in the negative electrode active material.
[0007] In some embodiments, 0.35≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) )≤0.5.
[0008] In some embodiments, the average particle size D of the negative electrode active material is V 50 is 10 μm to 18 μm. In some embodiments, the tap density of the negative electrode active material is 0.95 g / cm 3 ~1.15g / cm 3 In some embodiments, the specific surface area of the negative electrode active material is 1.5 m 2 / g~3.5m 2 / g.
[0009] In some embodiments, the graphite includes at least one of natural graphite and artificial graphite. In some embodiments, the amorphous carbon includes at least one of soft carbon and hard carbon.
[0010] The second aspect of the present invention provides a method for preparing the negative electrode active material, which comprises the following steps: coating graphite with an amorphous carbon precursor to obtain coated graphite; and isostatically pressing (or molding) the coated graphite.
[0011] In some embodiments, the method further comprises: heat treating the coated graphite after isostatic pressing; in some embodiments, the mass ratio of the amorphous carbon precursor to the graphite is (1-20): (80-99); in some embodiments, the coating treatment comprises at least one of gas phase coating, liquid phase coating and solid phase coating. In some embodiments, the amorphous carbon precursor comprises at least one of coal tar, petroleum tar, modified asphalt, mesophase asphalt, heavy oil, phenolic resin, epoxy resin and furfural resin; in some embodiments, the processing pressure of the molding or isostatic pressing treatment is 1MPa-200MPa; in some embodiments, the processing pressure of the molding or isostatic pressing treatment is 70MPa-160MPa; in some embodiments, the processing time of the isostatic pressing treatment is 1min-30min; in some embodiments, the processing time of the isostatic pressing treatment is 4min-25min.
[0012] In some embodiments, the heat treatment is carried out in a protective atmosphere; in some embodiments, the protective atmosphere includes at least one of a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, and a xenon atmosphere; in some embodiments, the temperature of the heat treatment is 800°C to 1400°C; in some embodiments, the temperature of the heat treatment is 1100°C to 1300°C; in some embodiments, the time of the heat treatment is 1h-72h; in some embodiments, the time of the heat treatment is 2h-10h; in some embodiments, the heating rate of the heat treatment is less than 20.0°C / min; in some embodiments, the heating rate of the heat treatment is 1.0°C / min to 5.0°C / min.
[0013] The third aspect of the present invention provides a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector, a negative electrode material layer is arranged on the negative electrode current collector, and the negative electrode material layer includes the above-mentioned negative electrode active material; and / or a negative electrode material layer is arranged on the negative electrode current collector, and the negative electrode material layer includes the negative electrode active material prepared by the above-mentioned method.
[0014] A fourth aspect of the present invention provides a secondary battery, which includes the above-mentioned negative electrode plate, positive electrode plate, electrolyte and separator.
[0015] A fifth aspect of the present invention provides a device comprising the secondary battery described above.
[0016] The present invention has the following beneficial effects:
[0017] 1. The negative electrode active material of the present invention comprises graphite and amorphous carbon coated on the surface of the negative electrode active material. The amorphous carbon coated on the surface can reduce the defects of the basal plane exposed on the graphite surface and reduce the embedding of solvent molecules, thereby reducing the cycle capacity decay of the battery. Moreover, the applicant surprisingly found that even if the coating layer is broken during charge and discharge, the graphite I 3R(101) and I 2H(101) Controlled within a specific ratio range, the core graphite can also inhibit the embedding of solvent molecules between graphite layers. Therefore, the specific structure of the surface-coated amorphous carbon and the core graphite cooperate with each other, greatly reducing the co-embedding of solvent molecules, thereby greatly improving the cycle performance of the negative electrode.
[0018] 2. The lithium ion secondary battery including the negative electrode active material of the present invention has an excellent cycle life. DETAILED DESCRIPTION
[0019] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0020] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0021] A list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0022] The term "D V "50" refers to the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%.
[0023] The negative electrode active material of the present invention comprises a core-shell structure of graphite and an amorphous carbon coating layer, wherein the amorphous carbon coating layer on the surface can prevent the electrolyte from directly contacting the end face of the graphite, thereby reducing the co-embedding of the solvent. Furthermore, the applicant surprisingly found that even if the coating layer is broken during the charge and discharge process, the I 3R(101) and I 2H(101) When controlled within a specific ratio, the graphite in the core can also inhibit the co-embedding of solvent molecules. Therefore, the present invention can significantly improve the cycle life of lithium-ion secondary batteries by cooperating with the specific structure of the surface-coated amorphous carbon and the core graphite. 3R(101) and I 2H(101) Satisfy the following relationship: 0.25≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) )≤0.5. When(I 3R(101) ×15 / 12) / (I3R(101) ×15 / 12+I 2H(101) ) is too small, the effect of the graphite in the inner core on inhibiting the embedding of solvent molecules into the graphite interlayer is weak, and the cycle capacity decay of the battery cannot be significantly reduced; when (I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) ) is too large, the graphite in the inner core reacts excessively with the non-aqueous electrolyte.
[0024] In some embodiments, 0.37≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) )≤0.47; in some embodiments, (I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) ) is selected from 0.25, 0.27, 0.29, 0.31, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47, 0.50 or any value therebetween.
[0025] In some embodiments, the average particle size D of the negative electrode active material is V 50 is 10 μm to 18 μm. In some embodiments, the average particle size D of the negative electrode active material is V 50 is 15 μm to 18 μm. In some embodiments, the average particle size D of the negative electrode active material is V 50 is 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm and 18μm.
[0026] In some embodiments, the tap density of the negative electrode active material after 1000 tapping treatments is 0.95 g / cm 3 ~1.2g / cm 3 If the tap density is too small, the coating property will be deteriorated when preparing the negative electrode; if the tap density is too large, the graphite needs to be additionally processed, which will increase the cost of graphite processing. In some embodiments, the tap density of the negative electrode active material after 1000 tap treatments is 1.05 g / cm 3 ~1.14g / cm 3 In some embodiments, the tap density of the negative electrode active material after 1000 tapping treatments is 0.95 g / cm 3 , 1.0g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 and 1.2 g / cm3 .
[0027] In some embodiments, the BET specific surface area of the negative electrode active material is 1.5 m 2 / g~3.5m 2 / g. If the BET specific surface area is too small, it becomes difficult to absorb Li during charging; on the contrary, if the BET specific surface area is too large, the reactivity of the negative electrode active material with the non-aqueous electrolyte increases. In some embodiments, the BET specific surface area of the negative electrode active material is 2.0 m 2 / g~3.0m 2 In some embodiments, the BET specific surface area of the negative electrode active material is 1.5 m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g and 3.5m 2 / g.
[0028] In some embodiments, the graphite is spheroidized. In some embodiments, the amorphous carbon on the surface of the graphite can be soft carbon or hard carbon, wherein the soft carbon or hard carbon is obtained by high temperature heat treatment of one or more of asphalt, heavy oil, anthracene oil, phenolic resin, and epoxy resin.
[0029] In some embodiments, the non-aqueous solvent includes propylene carbonate. In some embodiments, in the non-aqueous solvent, the mass fraction of the propylene carbonate is 30% to 60%.
[0030] The present invention first pulverizes and spheroidizes graphite, then purifies it through acid, and finally obtains the negative electrode active material through amorphous carbon coating, molding or isostatic pressing and heat treatment. In some embodiments, the pulverization treatment is at least one of air flow pulverization, ball milling and mechanical pulverization. In some embodiments, the spheroidization treatment is to repeatedly pulverize and grade the graphite in a spheroidization treatment device to spheroidize it. In some embodiments, the acid includes an inorganic acid; in some embodiments, the inorganic acid includes at least one of HCl, HF, H2SO4 and HNO3.
[0031] In some embodiments, the method further includes: before the coating treatment, acid-treating the graphite; in some embodiments, the mass ratio of the amorphous carbon precursor to the purified (acid-treated) graphite is (1-20):(80-99); in some embodiments, the mass ratio of the amorphous carbon precursor to the purified (acid-treated) graphite is 5:98, 8:98, 10:98, 15:98, 25:98, 5:93, 8:93, 10:93, 15:93, 25:93, 5:85, 8:85, 10:85, 15:85, 25:85, 35:85 or any range therebetween.
[0032] In some embodiments, the heat treatment temperature is 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or any range therebetween; in some embodiments, the heat treatment time is 2h, 4h, 6h, 8h, 10h, 12h, 20h, 40h, 50h, 60h, 72h or any range therebetween; in some embodiments, the heat treatment heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 10°C / min, 15°C / min in, 20°C / min, or any range therebetween; in some embodiments, the treatment pressure of the isostatic pressing treatment is 1 MPa, 20 MPa, 40 MPa, 80 MPa, 120 MPa, 140 MPa, 160 MPa, 1680 MPa, 190 MPa, 200 MPa, or any range therebetween; in some embodiments, the treatment time of the isostatic pressing treatment is 1 min, 6 min, 11 min, 16 min, 20 min, 23 min, 25 min, 27 min, 30 min, or any range therebetween.
[0033] The average particle size D of the graphite particles G in the following examples and comparative examples is V 50. For the determination of tap density and specific surface area, refer to GB / T 24533-2019.
[0034] The X-ray diffraction spectra of the graphite particles G in the following examples and comparative examples were measured as follows: using copper target Kα X-rays, scanning angles of 10 to 90°, scanning steps of ≤0.02°, and scanning speeds of 1° / min. The peaks between 43.0 and 44.0° in the XRD spectrum are the diffraction peaks of the rhombohedral phase (3R) (101), and the peaks between 44.0 and 45.0° are the diffraction peaks of the hexagonal phase (2H) (101).
[0035] The test methods and test results of the lithium ion battery performance in the following examples and comparative examples are as follows:
[0036] Cycle performance test method: At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a 1C rate and discharged at a 1C rate, and full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0037] Examples and Comparative Examples
[0038] Example 1
[0039] (1) Preparation of positive electrode sheet
[0040] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 96:2:2, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed, slit, and cut into pieces to obtain a positive electrode sheet.
[0041] (2) Preparation of negative electrode sheet
[0042] Graphite particles G, conductive agent acetylene black, thickener CMC and binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water is added, and the mixture is stirred under a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed, slit, and cut into pieces to obtain a negative electrode sheet. The preparation of the graphite particles G is as follows:
[0043] (a) Flake graphite (natural graphite) with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and subjected to multiple crushing and classification treatments to obtain spheroidized graphite particles A. In the obtained graphite particles A, the particle size D based on volume is V 50 is 15.6μm, and the tap density after 1000 tapping treatments is 0.96g / cm 3 The specific surface area based on the BET method is 6.2 m 2 / g;
[0044] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0045] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V50 Asphalt with a particle size of 2.6 μm is put into a high-speed mixer at a weight ratio of 92:8 and mixed thoroughly to obtain mixed powder C;
[0046] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 100 MPa for 5 min to obtain a composite block D;
[0047] (e) heating the composite block D to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 6 h to obtain a carbonized composite block E;
[0048] (f) Put the composite block E into a crusher and crush it to D V 50 is 16.4 μm, and then after demagnetization and screening, graphite particles G are obtained.
[0049] Among them, in the obtained graphite particles G, the volume-based particle size D V 50 is 16.2μm, and the tap density is 1.09g / cm 3 The specific surface area based on the BET method is 2.8 m 2 / g.
[0050] (3) Preparation of electrolyte
[0051] LiPF6 was dissolved in a mixed solvent of propylene carbonate, ethyl methyl carbonate and diethyl carbonate (volume ratio of 1:1:1), and 10 wt% of fluoroethylene carbonate was added as a film-forming additive to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0052] (4) Isolation film: polyethylene film
[0053] (5) Preparation of lithium-ion batteries
[0054] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery core; the bare battery core is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0055] Example 2
[0056] The steps of Example 2 are the same as those of Example 1, except that, in Example 2, the graphite particles are prepared as follows:
[0057] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V50 is 15.6μm, and the tap density after 1000 tapping treatments is 0.96g / cm 3 The specific surface area based on the BET method is 6.2 m 2 / g;
[0058] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0059] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 2.6 μm asphalt is put into a high-speed mixer at a weight ratio of 92:8 and fully mixed to obtain mixed powder C;
[0060] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 120 MPa for 20 min to obtain a composite block D;
[0061] (e) heating the composite block D to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 6 h to obtain a carbonized composite block E;
[0062] (f) Put the composite block E into a crusher and crush it to D V 50 is 16.6 μm, and then after demagnetization and screening, graphite particles G are obtained.
[0063] In the graphite particles G obtained above, the volume-based particle size D V 50 is 16.5μm, and the tap density is 1.08g / cm 3 The specific surface area based on the BET method is 2.9 m 2 / g.
[0064] Example 3
[0065] The steps of Example 3 are the same as those of Example 1, except that, in Example 3, the graphite particles are prepared as follows:
[0066] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V 50 is 15.6μm, and the tap density after 1000 tapping treatments is 0.96g / cm 3 The specific surface area based on the BET method is 6.2 m2 / g;
[0067] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0068] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 asphalt with a weight ratio of 2.6 μm is put into a high-speed mixer and fully mixed to obtain mixed powder C;
[0069] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 80 MPa for 20 min to obtain a composite block D;
[0070] (e) heating the composite block D to 1150° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1150° C. for 4 h to obtain a carbonized composite block E;
[0071] (f) Put the composite block E into a crusher and crush it to D V 50 is 16.8 μm, and then after demagnetization and screening, graphite particles G are obtained;
[0072] In the graphite particles G obtained above, the volume-based particle size D V 50 is 16.6μm, and the tap density is 1.12g / cm 3 The specific surface area based on the BET method is 2.7 m 2 / g.
[0073] Example 4
[0074] The steps of Example 4 are the same as those of Example 1, except that, in Example 4, the graphite particles are prepared as follows:
[0075] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V 50 is 11.5μm, and the tap density after 1000 tapping treatments is 0.83g / cm 3 The specific surface area based on the BET method is 8.6 m 2 / g;
[0076] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0077] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 asphalt with a weight ratio of 2.6 μm is put into a high-speed mixer and fully mixed to obtain mixed powder C;
[0078] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 100 MPa for 10 min to obtain a composite block D;
[0079] (e) heating the composite block D to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 4 h to obtain a carbonized composite block E;
[0080] (f) Put the composite block E into a crusher and crush it to D V 50 is 12.4 μm, and then after demagnetization and screening, graphite particles G are obtained.
[0081] Among them, in the obtained graphite particles G, the volume-based particle size D V 50 is 12.2μm, and the tap density is 1.03g / cm 3 The specific surface area based on the BET method is 3.1 m 2 / g.
[0082] Example 5
[0083] The steps of Example 5 are the same as those of Example 1, except that, in Example 5, the preparation of graphite particles is as follows:
[0084] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V 50 is 15.6μm, and the tap density after 1000 tapping treatments is 0.96g / cm 3 The specific surface area based on the BET method is 6.2 m 2 / g;
[0085] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0086] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 asphalt with a weight ratio of 2.6 μm is put into a high-speed mixer and fully mixed to obtain mixed powder C;
[0087] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 150 MPa for 5 min to obtain a composite block D;
[0088] (e) heating the composite block D to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 6 h to obtain a carbonized composite block E;
[0089] (f) Put the composite block E into a crusher and crush it to D V 50 is 17.8μm, and then after demagnetization and screening, graphite particles G are obtained.
[0090] In the graphite particles G obtained above, the volume-based particle size D V 50 is 17.5μm, and the tap density is 1.15g / cm 3 The specific surface area based on the BET method is 3.2 m 2 / g.
[0091] Example 6
[0092] The steps of Example 6 are the same as those of Example 1, except that, in Example 6, the graphite particles are prepared as follows:
[0093] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V 50 is 17.3μm, and the tap density after 1000 tapping treatments is 0.98g / cm 3 The specific surface area based on the BET method is 5.6 m 2 / g;
[0094] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0095] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 asphalt with a weight ratio of 2.6 μm is put into a high-speed mixer and fully mixed to obtain mixed powder C;
[0096] (d) putting the mixed powder C obtained above into an isostatic press and processing it at a pressure of 150 MPa for 15 min to obtain a composite block D;
[0097] (e) heating the composite block D to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 4 h to obtain a carbonized composite block E;
[0098] (f) Put the composite block E into a crusher and crush it to D V 50 is 17.8μm, and then after demagnetization and screening, graphite particles G are obtained.
[0099] In the graphite particles G obtained above, the volume-based particle size D V 50 is 17.6μm, and the tap density is 1.12g / cm 3 The specific surface area based on the BET method is 3.3 m 2 / g.
[0100] Comparative Example 1
[0101] The steps in Comparative Example 1 are the same as those in Example 1, except that, in Comparative Example 1, the graphite particles are prepared as follows:
[0102] (a) Flake graphite with a particle size of less than 100 mesh is placed in a spheroidizing treatment device, and spheroidized graphite particles A are obtained by multiple crushing and classification treatments. In the obtained graphite particles A, the particle size D based on volume is V 50 is 15.6μm, and the tap density after 1000 tapping treatments is 0.96g / cm 3 The specific surface area based on the BET method is 6.2 m 2 / g;
[0103] (b) the graphite particles A obtained above were put into an acidic solution containing 20% HF at a mass ratio of 1:1, mixed and stirred for 6 hours, filtered, and then the filter residue was put into an acidic solution containing 5% HCl and 25% HNO3 at a mass ratio of 1:1, and after sufficient reaction, it was filtered and washed with water for multiple times, and finally dried to obtain purified graphite particles B;
[0104] (c) The graphite particles B obtained above are pulverized and the particle size D of the volume basis is V 50 2.6 μm asphalt is put into a high-speed mixer at a weight ratio of 92:8 and fully mixed to obtain mixed powder C;
[0105] (d) heating the mixed powder C to 1250° C. at a heating rate of no more than 5° C. / min under a nitrogen atmosphere, and maintaining the temperature at 1250° C. for 6 h to obtain a carbonized composite powder D;
[0106] (e) The composite powder D is put into a crusher and crushed to D V 50 is 16.1 μm, and then after demagnetization and screening, graphite particles E are obtained.
[0107] In the graphite particles E obtained above, the volume-based particle size D V 50 is 16.0μm, and the tap density is 1.05g / cm 3 The specific surface area based on the BET method is 2.4 m 2 / g.
[0108] The parameters of the negative electrode active materials in Examples 1-6 and Comparative Example 1 and the cycle performance test results of the lithium ion battery are shown in Table 1.
[0109]
[0110]
[0111] It can be seen from Table 1 that the I of graphite in the negative electrode active material of the present invention is 3R(101) and I 2H(101) The specific ratio range is met and a lithium ion battery including the negative electrode active material has excellent cycle performance.
[0112] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A negative electrode active material comprising graphite and a coating layer located on the surface of the graphite and comprising amorphous carbon, wherein the graphite satisfies the following relationship: 0.25≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) )≤0.5, in, I 3R(101) is the peak intensity of the X-ray diffraction peak of the rhombohedral phase 101 crystal plane of graphite in the negative electrode active material, wherein I 2H(101) is the peak intensity of the X-ray diffraction peak of the hexagonal phase 101 crystal plane of graphite in the negative electrode active material.
2. The negative electrode active material according to claim 1, characterized in that 0.35≤(I 3R(101) ×15 / 12) / (I 3R(101) ×15 / 12+I 2H(101) )≤0.5。 3. The negative electrode active material according to claim 1, characterized in that The average particle size D of the negative electrode active material V 50 is 10 μm to 18 μm; and / or The tap density of the negative electrode active material is 0.95 g / cm 3 ~1.2g / cm 3 ; and / or The specific surface area of the negative electrode active material is 1.5 m 2 / g~3.5m 2 / g.
4. The negative electrode active material according to claim 1, characterized in that The graphite includes at least one of natural graphite and artificial graphite; and / or The amorphous carbon includes at least one of soft carbon and hard carbon.
5. A method for preparing the negative electrode active material according to any one of claims 1 to 4, comprising the following steps: The graphite is coated with an amorphous carbon precursor to obtain coated graphite; The coated graphite is subjected to isostatic pressing.
6. The method according to claim 5, characterized in that The method further comprises: after the isostatic pressing, heat treating the coated graphite; and / or The mass ratio of the amorphous carbon precursor to the graphite is (1-20):(80-99); and / or The coating treatment includes at least one of gas phase coating, liquid phase coating and solid phase coating; and / or. The amorphous carbon precursor includes at least one of coal tar pitch, petroleum tar pitch, modified tar pitch, mesophase tar pitch, heavy oil, phenolic resin, epoxy resin and furfural resin; and / or The treatment pressure of the isostatic pressing treatment is 1 MPa to 200 MPa; and / or The isostatic pressing treatment takes 1 to 30 minutes.
7. The method according to claim 6, characterized in that The heat treatment temperature is 800°C to 1400°C; and / or The heat treatment time is 1h-72h; and / or The heating rate of the heat treatment is below 20.0°C / min.
8. A negative electrode sheet, comprising a negative electrode current collector, on which a negative electrode material layer is arranged, and the negative electrode material layer comprises the negative electrode active material according to any one of claims 1-4; and / or on which a negative electrode current collector is arranged a negative electrode material layer, and the negative electrode material layer comprises the negative electrode active material prepared by the method according to any one of claims 5-7. 9 . A secondary battery comprising the negative electrode sheet, the positive electrode sheet, an electrolyte and a separator as claimed in claim 8 .
10. A device comprising the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary cell
CN102224623A